Gamification in Learning Newton's Laws: Enhancing Students’ Problem-Solving Skills - Sari, Ika Mustika; Ghinatri, Nurma; Saepuzaman, Duden; Amsor, Amsor (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
This research aims to determine students' problem-solving skills after using tournament-based online truth or dare media (New Todame). The effectiveness was measured at the implementation stage using a One-Group pretest-posttest design on 52 eleventh-grade IPA (Natural Science) students in one of the public high schools in Bandung City. The sampling technique employed was the purposive sampling technique. The testing techniques used were the normality test (Kolmogorov-Smirnov), the non-parametric Wilcoxon test, and the N-Gain test. Data collection was done by interview, preliminary study questionnaire, validation sheet, feasibility questionnaire, and pretest & posttest sheets. The results showed that the New Todame media was effective in improving students’ problem-solving skills on Newton's law material. The normality test (Kolmogorov-Smirnov) showed Sig. Value of less than 0.05, so that the Wilcoxon test was needed. The Wicoxon test results showed a significant difference in the average pretest and posttest, indicated by five aspects of problem-solving skills having an Asym.Sig value of 0.000. In addition, the increase in problem-solving skills on Newton's law material after students use New Todame media shows an N-Gain of 0.455 in the medium category